Cost‐effectiveness of multidisciplinary collaborative care versus usual care in the management of high‐risk patients with diabetes in Singapore: Short‐term results from a randomized controlled trial. (25th April 2018) - Siaw, M. Y. L.; Malone, D. C.; Ko, Y.; Lee, J. Y.‐C.
Summary: What is known and objective: Economic evidence of multidisciplinary collaborative care on glycaemic improvement in uncontrolled diabetic patients is limited. Therefore, the primary objective of this study was to assess the cost‐effectiveness of multidisciplinary collaborative care versus usual care and the secondary objective was to assess the cost‐effectiveness of these two care approaches in relation to varying glycaemic control of patients. Methods: An economic evaluation based on a six‐month randomized controlled trial involving high‐risk uncontrolled diabetic Asian patients with polypharmacy and multiple comorbidities was conducted from a healthcare institution perspective. The control arm received usual care, while the intervention arm received multidisciplinary care with regular clinical pharmacist follow‐up in addition to usual care. The study outcomes included glycated haemoglobin (HbA1c) change and total direct outpatient medical costs for diabetes‐related care. The cost‐effectiveness analyses were conducted for both arms and those stratified according to baseline HbA1c (Group 1:HbA1c 7.1%‐7.9%, Group 2:HbA1c ≥8.0%). The incremental cost per glycaemic improvement (HbA1c improvement of 0.1% and above) per patient was examined followed by uncertainty evaluation via probabilistic sensitivity analyses. A range of willingness‐to‐pay (WTP) thresholds (US165.21 to US5000.00 per glycaemic improvement) was used in analysis. Results and discussion: Overall, the intervention arm had greater improvement in HbA1c (I: mean −0.4% [95% CI −0.6 to −0.2] vs C: mean −0.1% [95% CI −0.2 to 0.1]; P = .014) and lower mean total direct outpatient medical costs per patient in comparison with the control arm (I: US516.77 ± 222.10 vs C: US607.78 ± 268.39; P < .001). The intervention arm was the dominant strategy across varying baseline HbA1c with higher probability of Group 2 being cost‐effective at higher WTP threshold. What is new and conclusions: The multidisciplinary collaborative care arm was cost‐effective in managing Asian patients with varying baseline HbA1c control. The multidisciplinary collaborative care also showed greater probability of being cost‐effective among Asian patients with poorly uncontrolled glycaemia.